Permanent Whisker Removal Reduces the Density of c-Fos+ Cells and the Expression of Calbindin Protein, Disrupts Hippocampal Neurogenesis and Affects Spatial-Memory-Related Tasks - Gonzalez-Perez, Oscar; López-Virgen, Verónica; Ibarra-Castaneda, Nereida (Frontiers in Cellular Neuroscience, 2018)
Facial vibrissae, commonly known as whiskers, are the main sensitive tactile system in rodents. Whisker stimulation triggers neuronal activity that promotes neural plasticity in the barrel cortex and helps create spatial maps in the adult hippocampus. Moreover, activity-dependent inputs and calcium homeostasis modulate adult neurogenesis. Therefore, the neuronal activity of the barrel cortex possibly regulates hippocampal functions and neurogenesis. To assess whether tactile information from facial whiskers may modulate hippocampal functions and neurogenesis, we permanently eliminated whiskers in CD1 male mice and analyzed the effects in cellular composition, molecular expression and memory processing in the adult hippocampus. Our data indicated that the permanent deprivation of whiskers reduced in 4-fold the density of c-Fos+ cells (a calcium-dependent immediate early gene) in cornu ammonis subfields (CA1, CA2 and CA3) and 4.5-fold the dentate gyrus. A significant reduction in the expression of calcium-binding proteincalbindin-D28k was also observed in granule cells of the dentate gyrus. Notably, these changes coincided with an increase in apoptosis and a decrease in the proliferation of neural precursor cells in the dentate gyrus, which ultimately reduced the number of BrdU+NeuN+ mature neurons generated after whisker elimination. These abnormalities in the hippocampus were associated with a significant impairment of spatial memory and navigation skills. This is the first evidence indicating that tactile inputs from vibrissal follicles strongly modify the expression of c-Fos and calbindin in the dentate gyrus, disrupt different aspects of hippocampal neurogenesis, and support the notion that spatial memory and navigation skills strongly require tactile information in the hippocampus.